Incidence of Primary Glaucoma in a Cohort of Nuclear Workers - E. V. Bragin; T. V. Azizova; M. V. Bannikova; A. G. Grinyov (Oftalʹmologiâ)
Objective: The study was aimed to estimate primary glaucoma incidence in a cohort of nuclear workers occupationally exposed to ionizing radiation over prolonged periods.Materials and methods. The cohort considered in the study included workers of the Mayak Production Association. All glaucoma cases that were reported in the study worker cohort regardless of its type were identified using the medical and dosimetry database ‘Clinic’. Statistical analyses were performed to estimate non-standardized (crude) and standardized incidence rates for primary glaucoma. Standardization was carried out indirectly using age distribution for the whole cohort as an internal reference. Incidence rates were estimated per 1000 person-years in accordance with conventional medical statistics.Results. At the end of the follow-up period, 476 primary glaucoma cases were reported in the study worker cohort over 482,217 person-years of the follow-up. The standardized primary glaucoma incidence was estimated to be 1.00 ± 0.05 in males and 0.70 ± 0.07 in females. Crude primary glaucoma estimates in both males and females increased with the increasing attained age of the workers. Crude incidence rates in males were significantly higher than in females for age 50–69. The standardized primary glaucoma incidence in males was also significantly increased compared to females. The standardized primary glaucoma incidence rates were increasing throughout the period from 1960s to the end of the follow-up.